Digital Media Contents for Children - Mumcu, Tuba (Fırat University, 2024)
With the advancement of technology, the technology-supported content that children are exposed to also varies. Although this situation has positive aspects, it also has negative aspects. In this sense, it is extremely important to analyze the digital media content that children are exposed to. Children are not capable of deciding which content is beneficial or harmful for them. Therefore, parents and educators have great duties. In this study, YouTube, one of the most used digital media content by children, the most downloaded games and applications by children, and innovations developed for children such as YouTube Kids, Messenger Kids and Kids Place were mentioned. Measures and precautions that can be taken against possible negative situations that children may encounter on these platforms are presented. Digital media content is used by children with special needs as well as children with normal development. In this direction, applications developed for children with special needs such as Gedex and I'm in Special Education were also included. In addition, to provide easy access to these applications, QR codes of the relevant applications were placed.

Teknolojinin ilerlemesi ile birlikte çocukların maruz kaldıkları teknoloji destekli içerikler de farklılık göstermektedir. Bu durumun her ne kadar olumlu yönleri bulunsa da olumsuz yönleri de bulunmaktadır. Bu anlamda çocukların maruz kaldıkları dijital medya içeriklerinin incelenmesi son derece önem arz etmektedir. Çocuklar hangi içeriklerin onlar için faydalı ya da zararlı olduğuna karar verebilecek yetide değillerdir. Bu yüzden ebeveynlere ve eğitimcilere büyük görev ve sorumluluklar düşmektedir. Bu çalışmada, çocuklar tarafından en çok kullanılan dijital medya içeriklerinden YouTube’tan, yine çocuklar tarafından en çok indirilen oyun ve uygulamalardan, YouTube Kids, Messenger Kids ve Kids Place gibi çocuklar için geliştirilen yeniliklerden bahsedilmiştir. Bu platrofmlarda çocukların olası karşılaşabilecekleri olumsuz durumlara karşı alınabilecek tedbir ve önlemler sunulmuştur. Dijital medya içerikleri normal gelişim gösteren çocukların yanı sıra özel gereksinimli çocuklar tarafından da kullanılmaktadır. Bu doğrultuda özel gereksinimli çocuklar için geliştirilen Gedex, Özel Eğitimdeyim gibi uygulamalara da yer verilmiştir. Ayrıca, bu uygulamalara kolay erişimin sağlanması amacıyla ilgili uygulamalara ait karekodlar yerleştirilmiştir.
ÇOCUKLAR İÇİN DİJİTAL MEDYA İÇERİKLERİ
Keywords: Child Development Education; Çocuk Gelişimi Eğitimi